Development of a cost-effective system for ovoviviparous production of Artemia nauplii at low-salinity as live food for the larvae of the African catfish (Clarias gariepinus: Burchell, 1822) - Bwala, Richard (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.